Legal Force of a Notarial Peace Deed Between the Victim and the Perpetrator in Termination of a Criminal Case at the Investigation Level in the Jurisdiction of the Riau Regional Police. - Suharizal, Suharizal; Arifullah, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study discusses the legal force of the Notarial Peace Deed between the Victim and the Perpetrator in the Termination of Criminal Cases at the Investigation Level in the Riau Regional Police Jurisdiction. The focus of the research is directed to analyze the position and evidentiary value of the notarial peace deed in the settlement of criminal cases, especially the crime of forgery of documents. The method used is a normative juridical approach by examining laws and regulations, doctrines, and case studies. Data were obtained through literature studies and analysis of the peace deed that was the object of the research. The results of the study indicate that the notarial peace deed is an authentic deed as regulated in Article 1868 of the Civil Code, which has perfect evidentiary force both formally and materially. However, in the context of criminal law, the existence of the deed does not automatically stop the investigation process, because the termination of the case is the authority of the investigator based on Article 109 of the Criminal Procedure Code. The peace deed only functions as a substantive consideration for the application of restorative justice, with the condition that there is a peace agreement, recovery of losses, and no objections from the victim or the public interest. This research confirms that notarial deeds play a crucial role as legal instruments that provide certainty and legitimacy to settlement agreements, both in civil and criminal matters. However, within the framework of positive law, their implementation still requires investigator discretion to determine whether to terminate a case.